Can anyone solve this using Natural Deduction rules? (ND)
I have attached a file showing the same problem with better symbols.
I ^ ~(TvD) -> R given
D^N -> V given
I -> ~T given
N^~V -> R goal
Thank you !!!
I don't think it follows. I assume the parentheses are as follows:I ^ ~(TvD) -> R given
D^N -> V given
I -> ~T given
N^~V -> R goal
(I /\ ~(T \/ D)) -> R given
(D /\ N) -> V given
I -> ~T given
(N /\ ~V) -> R goal
Then what happens when I, V, R, D are false and T, N are true?
If you can wait, I could look into this tomorrow morning. I like natural deduction!
Hell, true; I don't know why when I saw the first formula true I deduced R was true... And I made that mistake twice before posting
I don't know, I would have put the parentheses exactly as you did. Unless in the first formula, we have to read
$\displaystyle I\wedge (\neg(T\vee D)\rightarrow R)$ (but I find that strange)
the problem statement may be wrong.
$\displaystyle
(I\wedge \neg(T\vee D)) \rightarrow R\:\:\: given $
$\displaystyle (D\wedge N) \rightarrow V \qquad\;\quad\: given $
$\displaystyle I \rightarrow \neg T \qquad\qquad\qquad given $
$\displaystyle (N\wedge \neg V ) \rightarrow R \qquad\quad goal
$
So thats more like!! The problem statements are correct I ve just put also the parentheses to make it easier to read.
(Anyone can eliminate the parentheses using the parenthesis elimination rules!!) ! So any ideas...??